Strategy For Strengtheningins Institutions in Corn Development - Salman,; Syafiuddin,; Jumiati, (JURNAL AGRIBISAINS, 2025)
The urgency of this research lies in the need to strengthen institutional capacity as a prerequisite for enhancing the productivity and competitiveness of maize farmers, and as a collective instrument to address market and policy dynamics. This study aims to identify internal and external factors, as well as to determine appropriate strategies for institutional strengthening of the Padang Roppo Farmer Group in Tallu Bamba Village, Enrekang Sub-district, Enrekang Regency. A qualitative approach with descriptive analysis was applied, using purposive sampling to select 16 informants. Data were obtained from both primary and secondary sources through observation, interviews, and documentation. The results indicate that internal factors consist of five strengths and three weaknesses (total score: 3.46), while external factors consist of three opportunities and two threats (total score: 3.53). The IE matrix places the group in Quadrant I (“grow and build”), and SWOT analysis produces four alternative strategies: SO, WO, ST, and WT. The findings suggest the need for local government intervention through sustainable institutional empowerment programs, financing facilitation, and integration of institutional development with maize commodity programs at the village level.